The Effect of Perineal Massage on Perineal Tear Case on Primigravida Pregnant Mothers In Their Third Trimester In Public Health Center Care of Morokay 2018 - Indrayani, Triana; Tuasikal, Nurabia (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research aimed to find out the effect of perineal massage on the perineal tear in primigravida pregnant women trimester III in Morokay Public Health Center in 2018. The research used a Quasi-experimental design. The sampling technique used purposive random sampling. The sample was obtained by 32 respondents divided into 2 groups, 16 respondents were given perineal massage and 16 respondents were not given perineal massage.The data were analyzed using Mann Whitney Test. The results showed that there were differences of perineal tear in experimental group and the control group with a p-value (0.005). There was a difference in the incidence of perineal tear between groups carried out perineal massage and those with no perineal massage. Perineal massage can reduce the risk of perineal tear. It is important to be informed and applied that massage is one of the non-pharmacological interventions to prevent perineal rupture